UI/UX APLIKASI BUMDES SUKATANI BERBASIS MOBILE MENGGUNAKAN METODE DESIGN THINKING DENGAN PENGUJIAN SYSTEM USABILITY SCALE - Moch Taufik; Mochzen Gito Resmi; Uus Muhammad Husni Tamyiz (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
BUMDES or Village Owned Enterprises is a business unit owned by the village government. One of the goals of establishing BUMDES in every village in Indonesia is to improve the welfare of rural communities through several business units with economic value. But in reality, it is not easy to develop BUMDes, one of which is BUMDES Sukatani in Purwakarta Regency. Various problems faced by BUMDES Sukatani include administrative services that are still running manually, business unit management, and village potential that has not been fully utilized. Therefore, this research is helping to make it easier for residents to use services and make it easier for residents to sell, making it easier to find original products from the village. This research focuses on designing application recommendations by analyzing and designing UI/UX using the Design Thinking method. The design results were successfully tested on 21 respondents using the System Usability Scale (SUS) test with a result of 82.0, it can be stated that this design is acceptable (acceptable by the user).